2020
DOI: 10.1111/hae.14162
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐reacting recombinant porcine FVIII inhibitors in patients with acquired haemophilia A

Abstract: Acquired haemophilia A (AHA) is a rare haemostatic disorder caused by the production of autoantibodies to clotting factor VIII (FVIII). These antibodies primarily bind to the A2, C1 or C2 domains of endogenous FVIII, neutralizing the cofactor function. 1,2 The incidence of AHA is estimated at 1.48 per million population per year, of which 80%-90% of patients are elderly, 3 although there is also a reported association with pregnancy. 4 Patients with AHA often present with spontaneous bleeding and extensive sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…It is well tolerated, and the most frequent adverse event is the development of antibodies against r‐pFVIII. Two recent independent studies reported that cross‐reacting inhibitors were more frequent in people with anti‐hFVIII inhibitor titers >100 BU/mL 45,46 . Following drug approval, some case reports and studies on cohorts of people with acquired hemophilia A treated with r‐pFVIII have been published, all confirming susoctocog alfa good efficacy and safety for the management of severe bleeding episodes 47‐49 .…”
Section: Clinical Efficacy Of R‐pfviii In People With Acquired Hemophilia Amentioning
confidence: 95%
See 1 more Smart Citation
“…It is well tolerated, and the most frequent adverse event is the development of antibodies against r‐pFVIII. Two recent independent studies reported that cross‐reacting inhibitors were more frequent in people with anti‐hFVIII inhibitor titers >100 BU/mL 45,46 . Following drug approval, some case reports and studies on cohorts of people with acquired hemophilia A treated with r‐pFVIII have been published, all confirming susoctocog alfa good efficacy and safety for the management of severe bleeding episodes 47‐49 .…”
Section: Clinical Efficacy Of R‐pfviii In People With Acquired Hemophilia Amentioning
confidence: 95%
“…Two recent independent studies reported that cross-reacting inhibitors were more frequent in people with anti-hFVIII inhibitor titers >100 BU/mL. 45,46 Following drug approval, some case reports and studies on cohorts of people with acquired hemophilia A treated with r-pFVIII have been published, all confirming susoctocog alfa good efficacy and safety for the management of severe bleeding episodes. [47][48][49] A retrospective case series (n = 4 individuals with acquired hemophilia A) showed that this molecule is effective and safe.…”
Section: Clini C Al Effi C Ac Y Of R-pf Viii In People With Acqu Ired Hemophilia Amentioning
confidence: 99%
“…These inhibitors to human FVIII may cross‐react with porcine FVIII in some patients, though the affinity is lower than towards human FVIII 3 . Two European studies reported similar baseline cross‐reacting inhibitor incidence of approximately 44%–49% in patients diagnosed with AHA 24,25 …”
Section: Introductionmentioning
confidence: 93%
“…There are limited detailed reports of the time course of cross‐reacting rpFVIII inhibitors in patients undergoing treatment with rpFVIII out‐with clinical trials 25–31 . In some patients treated with rpFVIII no increase in cross‐reacting rpFVIII inhibitors were observed following therapy 26,28,29 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation